DESENVOLVIMENTO TECNOLÓGICO E CARACTERIZAÇÃO FÍSICO-QUÍMICA DE NANOPARTÍCULAS POLIMÉRICAS CONTENDO APOCININA - OLIVEIRA, JULIANA KOVALCZUK DE (2014)
Apocynin, also known as acetovanillone, is a methoxy-catechol described as a product originally extracted from the roots of Picrorhiza kurroa Royle (Scrophulariaceae). The most consistent studies involving apocynin are related to their effect on the pathophysiological mechanisms of NADPH oxidase inhibition, which represents an attractive therapeutic target for many diseases. However, apocynin has low solubility in water, and small dose-dependent therapeutic window, which are likely to influence their low bioavailability by oral route. The aim of this study was the development of polymeric nanoparticles containing apocynin from polymers PLA, PLA - PEG and bovine serum albumin (BSA), in order to improve their oral bioavailability characteristics. For quantification and determination of apocynin on nanoparticles encapsulation efficiency (EE%), it was developed and validated an analytical methodology in high performance liquid chromatography (HPLC). For morphological and physicochemical characterization of the nanoparticles, analysis of particle diameter and polydispersity index (PI), zeta potential (ZP), infrared spectroscopy (IR), X-ray diffraction (XRD), and differential scanning calorimetry (DSC) were performed. BSA nanoparticle containing apocynin showed the best results in relation to their morphological and physico-chemical characterization, especially in formulations with pH modification, in which the optimal composition had particles with reduced diameters, which were smaller than 300 nm, and rates of drug encapsulation efficiency ≥ 79.5 %. According to XRD and DSC, there was a decrease of crystallinity of apocynin after the nanoencapsulation process, thereby generating particles with better dissolution in water. Therefore, it can be concluded that BSA nanoparticles containing apocynin developed in this study have suitable morphological and physicochemical characteristics, which make them a potential drug delivery system.